Monolithic Chalcogenide Optical Nanocomposites Enable Infrared System Innovation: Gradient Refractive Index Optics. Issue 10 (27th March 2020) - Kang, Myungkoo; Sisken, Laura; Lonergan, Charmayne; Buff, Andrew; Yadav, Anupama; Goncalves, Claudia; Blanco, Cesar; Wachtel, Peter; Musgraves, J. David; Pogrebnyakov, Alexej V.; Baleine, Erwan; Rivero‐Baleine, Clara; et al.
Abstract: The size and weight of conventional imaging systems is defined by costly non‐planar lenses and the complex lens assemblies required to minimize optical aberrations. The ability to engineer gradient refractive index (GRIN) optics has the potential to overcome constraints of traditional homogeneous lenses by reducing the number of components in optical systems. Here, an innovative strategy to realize this goal based on monolithic GRIN media created in Ge‐As‐Se‐Pb chalcogenide infrared nanocomposites is presented. A gradient heat treatment to spatially modulate the volume fraction of high refractive index Pb‐rich nanocrystals within a glass matrix is utilized, providing a GRIN profile while maintaining an optical transparency. A first‐ever correlation of material chemistry and microstructure, processing protocol, and optical property modification resulting in a prototype GRIN structure is presented. The integrated approach and mechanistic understanding illustrated by this versatile modification paradigm provides a platform for new optical functionalities in next‐generation imaging applications. Abstract : Monolithic infrared gradient refractive index glass‐ceramic nanocomposites are achieved through a scalable thermal treatment of a starting chalcogenide glass. The mechanistic understanding enabled through correlation of glass chemistry and the ability to selectively form high refractive index nanocrystals within a Ge‐As‐Pb‐Se glass matrix enables the spatial and spectral tailoring of the composite's effective refractive index resulting in novel optical functionalities.